Determinants of Mental Health of Fishermen in Coastal Areas - Cholila, Cholila; Abdullah, Asnawi; Ichwansyah, Fahmi; Hermansyah, Hermansyah; Aramico, Basri (Indonesian Journal of Global Health Research, 2025)
Mental health is an aspect of health that is increasingly receiving global attention because of its significant impact on individual and community health problems. Mental health disorders have increased in coastal areas in the last 5 years. Mental health challenges are becoming increasingly complex in the most dominant jobs in coastal regions, such as in the profession of fishermen. In addition, there are still many people who experience mental disorders. This study aims to analyze fishermen's mental health determinants in the Coastal Area. This study uses a quantitative research type with a cross-sectional design. This study was conducted by interviewing using a questionnaire. The population in this study consisted of fishermen in the coastal area of Mesjid Raya District, especially MNS Keude, with as many as 456 fishermen. The sampling method used simple random sampling with a sample size of 82 respondents. Data were collected using a validated questionnaire. The results showed that there was a most dominant relationship between the number of children >2 (OR = 48.17; 95% CI = 1.68-1377.66; p = 0.024), moderate fatigue level (OR = 26.57; 95% CI = 1.59-444.89; p = 0.023) and age (OR = 0.66; 95% CI = 0.44-0.99; p = 0.049) most dominantly related to mental health disorders in fishermen in coastal areas. Fishermen who have more than two children are the most dominant factor in mental health problems.